Dynamic Drusen Remodelling in Participants of the Nutritional AMD Treatment-2 (NAT-2) Randomized Trial. - Giuseppe Querques; Bénédicte M J Merle; Nicole M Pumariega; Pascale Benlian; Cécile Delcourt; Alain Zourdani; Heather B Leisy; Michele D Lee; R Theodore Smith; Eric H Souied (PLoS ONE, 2016)
PURPOSE:To evaluate the dynamic remodeling of drusen in subjects with unilateral neovascular age-related macular degeneration (AMD) receiving a three-year course of oral docosahexaenoic acid (DHA) or placebo. SETTING:Institutional setting. METHODS:Three hundred subjects with age-related maculopathy and neovascular AMD in the fellow eye were randomly assigned to receive either 840 mg/day DHA or placebo for 3 years. Main outcome measures of this post-hoc sub-group analysis were progression of drusen number, total diameter, and total area on fundus photography, and their association with DHA supplementation, socio-demographic and genetic characteristics. RESULTS:Drusen progression was analyzed in 167 subjects that did not develop CNV (87 that received DHA and 80 that received placebo). None of the drusen remodeling outcomes were significantly associated with DHA supplementation. Total drusen diameter reduction in the inner subfield was significantly associated with age (older patients: r = -0.17; p = 0.003). Women showed a tendency to decreased total drusen diameter in the inner subfield with CFH polymorphism (p = 0.03), where women with TT genotype tended to have a greater reduction in drusen diameter than other genotypes (CC and CT). Drusen area in the inner subfield was more reduced in older patients (r = -0.17) and in women (p = 0.01). Drusen number showed no significant trends. CONCLUSIONS:Dynamic drusen remodeling with net reduction in drusen load over three years was found in patients with exudative AMD in one eye and drusen in the other eye (study-eye). This reduction was correlated with increased age and female gender, and showed a tendency to be influenced by CFH genotype, but did not appear to be affected by DHA supplementation. TRIAL REGISTRATION:Controlled-Trials.com ISRCTN98246501.